KARAKTERISTIK BERPIKIR MATEMATIS SISWA SMP MAJELIS TAFSIR AL-QURâAN (MTA) GEMOLONG DALAM MEMECAHKAN MASALAH MATEMATIKA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) DITINJAU DARI KEMAMPUAN PENALARAN SISWA DAN GENDER - Supriyanto, Agus; Mardiyana, Mardiyana; Subanti, Sri (Jurnal Pembelajaran Matematika, 2014)
Abstract: The aims of this research were to know and to describe mathematical thinking characteristic of grade VII students of SMP MTA Gemolong in solving mathematicÂ  problems at linear equation of two variables (LETV) observed from the reasoning capability and gender. This research belonged to descriptive research with qualitative explorative approach. The sample was taken by using purposive sampling technique. There were six samples used in this research. The category of the sample based on this reasoning ability was taken by reasoning test and space field test. There were two types of instruments that were used in this research to collect the data. The first was solving problem test instrument, and the second was interview guidance. Validation test of the data that was used in this research was time triangulation test. The results of this research indicated as follows. (1) The characteristic of mathematical thinking of male and female students with high reasoning ability in solving problems did not complete the phases of mathematical thinking, but it completed in the reproduction and connection phase. Whereas in analysis phaseit was not completed. (2) The characteristic of mathematical thinking of male and female students with intermediate reasoning ability in solving problems did not complete the phases of mathematical thinking, but it completed in the reproduction and the connection phase. Â Whereas in analysis phase, it was not completed. (3) The characteristic of mathematical thinking of male and female students with low reasoning ability in solving problems did not complete the phases of mathematical thinking, but it completed in the reproduction phase. Whereas in the connection and analysis phase, it was not completed.Keywords: mathematic thinking, solving problem, reasoning ability, gender